2014
DOI: 10.1108/imds-11-2013-0480
|View full text |Cite
|
Sign up to set email alerts
|

Intention to use mobile customer relationship management systems

Abstract: Purpose – The purpose of this paper is to investigate the behavioral intentions of business-to-business (B2B) sales managers to use mobile customer relationship management (CRM) systems in the course of their day-to-day activities. Design/methodology/approach – An extended Technology Acceptance Model (TAM) of mobile CRM system adoption is developed and tested with data from 105 international sales managers representing five B2B companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…mCRM B2B companies and mobile CRM systems developers can help understand key factors that can play a role in influencing the intent of adopting a CRM mobile system from the point of view of the sales manager. (Karjaluoto & Töllinen & Pirttiniemi & Jayawardhena 2014).…”
Section: Resultsmentioning
confidence: 99%
“…mCRM B2B companies and mobile CRM systems developers can help understand key factors that can play a role in influencing the intent of adopting a CRM mobile system from the point of view of the sales manager. (Karjaluoto & Töllinen & Pirttiniemi & Jayawardhena 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Karjaluoto et al (2014) and Muther (2012) demonstrated other five dimensions for CRM which are: solving problems, customers' database, service quality, CRM system integration and employee behavior, these dimensions that identify and satisfy the business needs.…”
Section: Customer Relationship Managementmentioning
confidence: 99%
“…Hollensen (2015) and Kumar and Reinartz (2012) identify two fundamental dimensions of CRM, which are (1) the human dimension and (2) the business dimension; in which the human dimension entails the recognition and response to the human needs of the customer, as well as the incorporation of gratitude and courtesy into customer service. In this case, acknowledging the concerns of the clients and defusing issues helps to enhance customer retention.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%